2021
DOI: 10.1001/jamapediatrics.2020.4719
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility of Escherichia coli Among Infants Admitted to Neonatal Intensive Care Units Across the US From 2009 to 2017

Abstract: IMPORTANCE Escherichia coli is a leading cause of serious infection among term and preterm newborn infants. Surveillance of antibiotic susceptibility patterns of E coli among infants admitted to neonatal intensive care units should inform empirical antibiotic administration.OBJECTIVE To assess the epidemiologic characteristics and antibiotic susceptibility patterns of E coli in infants admitted to neonatal intensive care units in the US over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 40 publications
4
36
1
Order By: Relevance
“…Although numbers are small, the Gram-negative antibiotic nonsusceptibility rate, remained unchanged. This is comparable to a recent study, from the USA where they found a stable E. coli nonsusceptibility rate during 2009–2017 ( 10 ). The nonsusceptibility rates were on the other hand substantially higher than in our study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Although numbers are small, the Gram-negative antibiotic nonsusceptibility rate, remained unchanged. This is comparable to a recent study, from the USA where they found a stable E. coli nonsusceptibility rate during 2009–2017 ( 10 ). The nonsusceptibility rates were on the other hand substantially higher than in our study.…”
Section: Discussionsupporting
confidence: 90%
“…The median (IQR) duration of antibiotic therapy for EOS declined from 14 (10)(11)(12)(13)(14) days in the period 1996-2006 compared to 8 (7-10) days in the period 2007-2018 (p < 0.013).…”
Section: Antibiotic Therapy and Susceptibilitymentioning
confidence: 96%
See 2 more Smart Citations
“…The rate of antibiotic resistant bacteria in our study was low compared to studies from other settings [36,37]. In a recent retrospective study between 2009 and 2017 from the USA, a mean of 5% ESBL-producingE.coli was seen in a large cohort (n = 733) of neonatal E-coli sepsis [38]. The proportion of all ESBL-producingEnterobacterales in our study, with a smaller sample size, was 7/107 (6.5%) and is still considered low.…”
Section: Discussioncontrasting
confidence: 62%